2021
DOI: 10.1101/2021.06.22.449410
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Similar neuronal imprint and absence of cross-seeded partner fibrils in α-synuclein aggregates from MSA and Parkinson’s disease brains

Abstract: Aggregated alpha–synuclein (α–syn) is a principal constituent of Lewy bodies (LBs) and glial cytoplasmic inclusions (GCIs) observed respectively inside neurons in Parkinson′s disease (PD) and oligodendrocytes in multiple system atrophy (MSA). Yet, the cellular origin, the pathophysiological role, and the mechanism of formation of these inclusions bodies (IBs) remain to be elucidated. It has recently been proposed that α–syn IBs eventually cause the demise of the host cell by virtue of the cumulative sequestrat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In none of these approaches did α-syn represented 50% of the content. In the most recent study performing a quantitative comparison of the proteomes composing LBs and glial cytoplasmic inclusions, Laferriere et al identified 1022 proteins resisting sarkosyl solubilization in these inclusions [ 27 ]. α-syn is by far the most significantly enriched protein in both types of samples, with a fold change of disease vs. control close to 40, while the second most enriched protein reaches a fold change of 10 [ 27 ].…”
Section: Contribution To the Debatementioning
confidence: 99%
See 1 more Smart Citation
“…In none of these approaches did α-syn represented 50% of the content. In the most recent study performing a quantitative comparison of the proteomes composing LBs and glial cytoplasmic inclusions, Laferriere et al identified 1022 proteins resisting sarkosyl solubilization in these inclusions [ 27 ]. α-syn is by far the most significantly enriched protein in both types of samples, with a fold change of disease vs. control close to 40, while the second most enriched protein reaches a fold change of 10 [ 27 ].…”
Section: Contribution To the Debatementioning
confidence: 99%
“…In the most recent study performing a quantitative comparison of the proteomes composing LBs and glial cytoplasmic inclusions, Laferriere et al identified 1022 proteins resisting sarkosyl solubilization in these inclusions [ 27 ]. α-syn is by far the most significantly enriched protein in both types of samples, with a fold change of disease vs. control close to 40, while the second most enriched protein reaches a fold change of 10 [ 27 ]. Therefore, we could state that α-syn is a prominent/overly represented constituent, but also emphasize the complex proteome of these inclusions, an overlooked information of paramount importance for understanding the nature and origin of these intracellular inclusions.…”
Section: Contribution To the Debatementioning
confidence: 99%